Mitskite oponenti na ranosrednovekovite pojasni jazičinjaMythical Opponents on Early Middle Ages Belt Tongues - Čausidis, Nikos (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The paper explores the iconography and symbolism of certain types of late Avarian belt tongues (7th - 8th centuries) which depict three figures (zoomorphic, zoo-anthropomorphic, or anthropomorphic), two of which are engaged in a combat. The author proceeds from a thesis that this scene depicts a symbolic struggle between two opposing gods, a representative of the celestial/luminous principle, and a representative of the htonic principle. The author cites arguments according to which this jewelry, and the scenes depicted on it, belonged to Pannonian Slavs or to other peoples which had participated in Slavic ethno-genesis.